Mood self-assessment in bipolar disorder: a comparison between patients in mania, depression, and euthymia - Silva,Rafael de Assis da (2013)
BACKGROUND: Some studies indicate that mood self-assessment is more severely impaired in patients with bipolar disorder in a manic episode than in depression. OBJECTIVES: To investigate variations in mood self-assessment in relation to current affective state in a group of individuals with bipolar disorder. METHODS: A total of 165 patients with a diagnosis of bipolar disorder type I or type II had their affective state assessed using the Clinical Global Impressions Scale for use in bipolar illness (CGI-BP), the Positive and Negative Syndrome Scale (PANSS), and the Global Assessment of Functioning (GAF). In addition, participants completed a self-report visual analog mood scale (VAMS). Patients were divided into three groups (euthymia, mania, and depression) and compared with regard to VAMS results. RESULTS: Manic patients rated their mood similarly to patients in euthymia in 14 out of 16 items in the VAMS. By contrast, depressed patients rated only two items similarly to euthymic patients. CONCLUSION: Patients with bipolar disorder in mania, but not those in depression, poorly evaluate their affective state, reinforcing the occurrence of insight impairment in the manic syndrome.